Eco-Venture: Implementasi Board Game ‘Geo-Race’ sebagai Edukasi Konservasi dan Geopark di SDN Tegal Caringin - Safa Anafirizkita; Najmi Firdaus; Rafli Maulana Mukhlis; Anindhia Laudza Trinanda; Muhammad Akbar Aqila; Mutiara Nurani; Alvina Kosasih; Thoriq Edriva Hammadi; Indah Valentina Pebriasi; Deswita Nur Alpharofi (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2026)
The Eco-Venture program was implemented at SDN Tegal Caringin, Ciemas District, Sukabumi Regency, involving 30 fifth-grade students. The program combined instructional delivery using PowerPoint media with an interactive educational game called Geo-Race, a snakes and ladders based board game equipped with environmental and geopark themed cards. This program aims to foster early awareness of the importance of environmental conservation based on the values of the Ciletuh-Palabuhanratu UNESCO Global Geopark. The study employed a pre-test and post-test design to assess changes in students' knowledge and attitudes, complemented by observations of student participation during the activities. Data analysis began with the Shapiro-Wilk normality test, followed by either the Paired Sample T-Test or the Wilcoxon Signed-Rank Test, depending on data distribution. The analysis showed a significant improvement in students’ knowledge (from 54.6 to 70.3; p=0.000) and attitudes (from 84.6 to 90; p=0.043) after participating in the program. Furthermore, the program encouraged collaboration among students, teachers, and the community in environmental protection, while also creating opportunities for sustainable economic development through the enhancement of geopark potential. The Geo-Race innovation proved effective as an interactive learning medium that strengthened students’ understanding of environmental conservation and local potential. The program is recommended for integration into the local content curriculum in schools across the geopark area to expand both educational and socio-economic impacts sustainably.